Sex-Related Differences in Clinical Presentation and Risk Factors for Mortality in Patients Hospitalized With Coronavirus Disease 2019 in New York City. (9th July 2021) - Mathad, Jyoti S; Lee, Myung Hee; Chalem, Andrea; Frey, Melissa K; Chapman-Davis, Eloise; Kopparam, Rohini V; Dayal, Ashlesha K; Wald, Gal; Pinheiro, Laura C; Satlin, Michael J; Goyal, Parag; Safford, Monika M; et al.
Abstract: We evaluated sex-related differences in symptoms and risk factors for mortality in 4798 patients hospitalized with coronavirus disease 2019 in New York City. When adjusted for age and comorbidities, being male was an independent predictor of death with mortality significantly higher than females, even with low severe acute respiratory syndrome coronavirus 2 viral load at admission.